2020
DOI: 10.1109/access.2020.3021354
|View full text |Cite
|
Sign up to set email alerts
|

Delay-Aware SFC Provisioning in Hybrid Fog-Cloud Computing Architectures

Abstract: Network function virtualization (NFV) technology enables service providers to implement software-based network processing functionalities on standard computing servers (nodes). As such, this approach mandates the need for mapping virtual network functions (VNFs) in service function chains (SFCs) on these nodes for incoming service requests. Now traditional VNF mapping schemes use cloud nodes for its abundant available resources, at the detriment of prolonged network delays. Alternative schemes use fog nodes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 36 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…All coarse-grained workloads are scheduled under their maximum threshold level to avoid any violence of users. The authors in [15][16][17][18][19] suggested that frameworks and architectures solve deadline-aware offloading and scheduling problems for IoT applications. They formulated problems as integer linear programming where all objective functions and constraints are linear and integer variables.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…All coarse-grained workloads are scheduled under their maximum threshold level to avoid any violence of users. The authors in [15][16][17][18][19] suggested that frameworks and architectures solve deadline-aware offloading and scheduling problems for IoT applications. They formulated problems as integer linear programming where all objective functions and constraints are linear and integer variables.…”
Section: Related Workmentioning
confidence: 99%
“…To obtain the complexity of the algorithms, the lightweight and linear search-based iterative model was devised by studies. The studies [13][14][15][16][17][18][19] devised different optimization heuristics based on Bundle branch-bound, Subgradient linear search, Interior-Points, and Cutting-plane Hungarian with different types of searching methods. These methods search for the best resource among edge/fog cloud nodes before allocating tasks to them.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Data Execution —The execution delay of the system calculated as [ 43 ]: where , , , and are the processing, queuing, transmission, and propagation delays of workloads in list , respectively. These delays are calculated as: where is traffic load and is the processing rate of a fog node.…”
Section: System Modelmentioning
confidence: 99%